O-BN09 The impact of the Covid-19 pandemic on benign upper GI surgery: The first 12 months at a single centre. (16th December 2021) - Michel, Martin; Fifer, Helen; Moran, Emily; Hammett, Felix; Bonner, Clare; Kronberga, Madara; Khawgali, Mohamed; Balbola, Mohamed; Saha, Arin
Abstract: Background: The road to recovery from the Covid-19 pandemic has started but no-one knows when it will end. 18 months on from the World Health Organisation declaring a global pandemic on the 11 th March 2020 this has had a dramatic impact on both acute and elective hospital services. Whilst, quite rightly, the focus has been on prioritising cancer resections during the pandemic, many patients awaiting benign operations are facing lengthy waiting times. The aim of this study was to quantify the impact of the COVID-19 pandemic on benign upper GI surgery at a single centre compared to previous operating activity levels. Methods: Retrospective analysis of computerised theatre records for the first 12 months of the pandemic (11 th March 2020-11 th March 2021) were compared to average historical data (HD) over the last five years (2015-2019) over the same time frame. Benign upper Gi operations included were cholecystectomy, anti-reflux/hiatus hernia repairs, cardiomyotomies and bariatric procedures. Results: Conclusions: The Covid-19 pandemic has dramatically affected benign upper GI surgery at our unit. Overall total operation numbers were down by 31% when compared to HD (440 vs 641). The largest deficit was in bariatrics where no bariatric surgery was performed during the first 12 months of the pandemic, which has restarted as of July 2021. There was also a 30% reduction in the number of cholecystectomies performed likely due to initial guidance recommending non-operative management at the start of the pandemic. Hiatal work numbers remained consistent. This quantitative study can direct future service delivery and help guide the post-pandemic recovery.